2020
DOI: 10.1039/d0ra07521c
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of structure, thermal and water vapor permeability barrier properties of poly(butylene succinate)/organomodified beidellite clay bionanocomposites prepared by in situ polycondensation

Abstract: The exploitation of beidellite clay (BDT), used as a nanofiller in the preparation of poly(butylene succinate) (PBS)/organoclay biodegradable nanocomposites, was investigated. Their thermal and water vapor barrier properties were also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 80 publications
6
23
1
Order By: Relevance
“…A linear relationship between the cloisite content and oxygen/water vapor permeability was found, showing a decrease of ~50% for both gases with 7 wt% of the OMMT [126], in a similar way as for the PLA/PBS-ran-PBA and PLA/PBS clay nanocomposites [127], whereas other authors reported a lower reduction of O 2 P in PLA/PBS blends (80/20 w/w) with Cloisite 30B [115]. A similar reduction was achieved for PBS nanocomposites with organically modified layered silicate (OMLS) [112,128], and organomodified beidellite clay nanocomposites [129]. For PBS-ran-PBA nanocomposites with native montmorillonite and OMMT, the gas permeabilities drop between 60% and 70% in water-injection-extruded PBS-ran-PBA/Cloisite 30B nanocomposites [113].…”
Section: Pbs-based Nanocompositessupporting
confidence: 63%
“…A linear relationship between the cloisite content and oxygen/water vapor permeability was found, showing a decrease of ~50% for both gases with 7 wt% of the OMMT [126], in a similar way as for the PLA/PBS-ran-PBA and PLA/PBS clay nanocomposites [127], whereas other authors reported a lower reduction of O 2 P in PLA/PBS blends (80/20 w/w) with Cloisite 30B [115]. A similar reduction was achieved for PBS nanocomposites with organically modified layered silicate (OMLS) [112,128], and organomodified beidellite clay nanocomposites [129]. For PBS-ran-PBA nanocomposites with native montmorillonite and OMMT, the gas permeabilities drop between 60% and 70% in water-injection-extruded PBS-ran-PBA/Cloisite 30B nanocomposites [113].…”
Section: Pbs-based Nanocompositessupporting
confidence: 63%
“…In view of the mechanical properties enhanced, some solutions are proposed: (i) blending; [8][9][10] (ii) process; 11,12 (iii) crosslinking; [13][14][15][16] (iv) copolymerization. 17 As a commonly used modification method in polymer materials, blending could not only improve performance, but sometimes reduce costs, which provides the possibility for the promotion of materials. 18 For example, Shuo Qiu 19 and Atcharawan Srisa 20 blended PBAT with PLA to improve the mechanical properties by adding nanopolyhedral oligomeric silsesquioxane and antibacterial properties by adding trans-cinnamaldehyde of film.…”
Section: Introductionmentioning
confidence: 99%
“…Although the increased diameter of the PLA/AS fibers can induce an increase of the WCA by reducing the specific surface of the mat, the slight increase in hydrophilicity observed for the PLA/AS systems can be ascribed to the presence of silicon dioxide on the nanosilica surface 87 . On the other hand, the more pronounced WCA reduction observed for PLA/CLO systems can be likely ascribed to the thinner fiber diameter observed by SEM and to the presence of the organo‐modified clays at the surface of the fibers, as highlighted by FTIR‐ATR measurements 88,89 …”
Section: Discussionmentioning
confidence: 97%
“… 87 On the other hand, the more pronounced WCA reduction observed for PLA/CLO systems can be likely ascribed to the thinner fiber diameter observed by SEM and to the presence of the organo‐modified clays at the surface of the fibers, as highlighted by FTIR‐ATR measurements. 88 , 89 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation